2018
DOI: 10.1002/lsm.23047
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of water‐soluble fluorescent antibody mediated by fractional Er:YAG laser for the diagnosis of lupus erythematosus in mice

Abstract: Objectives Although transdermal drug delivery system (TDDS) has been successfully used for delivering small molecules, its application in the delivery of diagnostic antibodies has been limited due to their large size. In this study, we aim to obtain a broad insight in the dynamics of TRITC‐conjugated Goat Anti‐Mouse IgG (T‐IgG) uptake in fractional Er:YAG laser pretreated skin and provide a new technical option for detecting lupus erythematosus (LE) in mice. Methods The skins of SD and MRL/lpr mice were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…However, recently it was shown that nivolumab and two other antibodies could be delivered by fractional lasers into pig or mouse skin in vitro and in vivo. 6,15,16 In a previous study, we showed enhanced uptake and biodistribution of nivolumab in vitro using AFL and intradermal pneumatic injection on pig skin. 6 However, the impact of AFL or intradermal injection on pharmacokinetics and biodistribution of nivolumab in vivo remains to be determined.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, recently it was shown that nivolumab and two other antibodies could be delivered by fractional lasers into pig or mouse skin in vitro and in vivo. 6,15,16 In a previous study, we showed enhanced uptake and biodistribution of nivolumab in vitro using AFL and intradermal pneumatic injection on pig skin. 6 However, the impact of AFL or intradermal injection on pharmacokinetics and biodistribution of nivolumab in vivo remains to be determined.…”
Section: Introductionmentioning
confidence: 95%
“…The molecular weight of antibodies like nivolumab are 150 kDa, being around 100–10,000 times larger than the above‐mentioned drugs. However, recently it was shown that nivolumab and two other antibodies could be delivered by fractional lasers into pig or mouse skin in vitro and in vivo 6,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, LADD has shown successful delivery of several smaller molecules (130-1415 Da) [12][13][14][15][16], and a few studies have also described the topical delivery of antibodies [19,37,38]. Two of these were by use of Er:YAG lasers, one in porcine skin in vitro [19], and another into mouse skin [37]. Furthermore, two studies have investigated the combination of AFL and anti-PD-1 antibody treatment of tumors in mice [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in laser-assisted delivery of very large molecules such as antibodies (150 kDa) has increased in the past 5 years [ 6 , 10 , 11 , 12 ]. Topical delivery of therapeutic antibodies could be an advantage for the treatment of various skin diseases, providing a topical, targeted treatment compared to systemic administration, whereby possible side effects might be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Topical delivery of therapeutic antibodies could be an advantage for the treatment of various skin diseases, providing a topical, targeted treatment compared to systemic administration, whereby possible side effects might be avoided. Three LADD studies successfully demonstrated the delivery of antibodies using an Er:YAG laser [ 6 , 11 , 12 ] and two studies from our lab showed delivery of the anti-PD-1 antibody nivolumab with an ablative fractional CO 2 laser [ 13 , 14 ]. Further, a recent study showed reduced tumor growth in mice after treatment with an ablative fractional CO 2 laser, followed by topical application of anti-PD-1 antibody coated patches, indirectly indicating a successful delivery of the anti-PD-1 antibody into mouse tumors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%